PENGARUH LKS BERORIENTASI MODEL PICTURE AND PICTURE DALAM PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR IPA SISWA KELAS VII SMPN 1 X KOTO SINGKARAK - Noka Hendra; Hamdi Rifai; Nurhayati Nurhayati (PILLAR OF PHYSICS EDUCATION, 2015)
The using of student worksheets oriented picture and picture models with contextual teaching and learning approach is expected to improve student learning outcomes and improve mindset, so that the material being studied by the students will be remembered longer. Moreover, it can increase the motivation and creativity of students in the learning and apply it in everyday life. This type of research is experimental research design with randomize control group only design. At this research using samples of two classes, namely the experimental class and control class. In the experiment class using a worksheet oriented picture and picture model with contextual teaching and learning approach, while grade control using ordinary worksheets by CTL approach. Data were analyzed by using the equality test two averages, simple regression test, and product moment correlation test on the real level on 0.05